Pemberdayaan Komunitas Berkelanjutan melalui Trilogi Pendidikan, Keluarga, dan Keagamaan di Desa Bedengung, Bangka Selatan - Aceng Zakaria; Syaeful Rokim; Indah Septiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service program aimed to empower the community of Bedengung Village, South Bangka, through an integrated trilogy approach of education, family, and religious development as a strategy for sustainable community empowerment. The program was conducted using a participatory descriptive qualitative approach from July to September 2025, involving Qur’anic learning center students, women’s religious study groups, youth, community leaders, and village officials. The activities included mentoring children’s Qur’an reading at Al-Anshori TPA, organizing regular religious gatherings for mothers, implementing social and philanthropic initiatives through the distribution of donated clothing for disadvantaged groups, and providing handicraft training based on recycled materials to strengthen the local creative economy. The results indicated improvements in children’s religious literacy, the strengthening of mothers’ roles in family resilience, increased social solidarity among residents, and the development of community skills and entrepreneurial interest based on local potential. Active community participation and strong support from the village government were key factors contributing to the program’s success. This program concludes that integrating education, family, and religious values can serve as a holistic and sustainable model for village community empowerment.